Adaptation of the microdosimetric kinetic model to hypoxia. (7th October 2016) - Bopp, C; Hirayama, R; Inaniwa, T; Kitagawa, A; Matsufuji, N; Noda, K
Abstract: Ion beams present a potential advantage in terms of treatment of lesions with hypoxic regions. In order to use this potential, it is important to accurately model the cell survival of oxic as well as hypoxic cells. In this work, an adaptation of the microdosimetric kinetic (MK) model making it possible to account for cell hypoxia is presented. The adaptation relies on the modification of damage quantity (double strand breaks and more complex lesions) due to the radiation. Model parameters such as domain size and nucleus size are then adapted through a fitting procedure. We applied this approach to two cell lines, HSG and V79 for helium, carbon and neon ions. A similar behaviour of the parameters was found for the two cell lines, namely a reduction of the domain size and an increase in the sensitive nuclear volume of hypoxic cells compared to those of oxic cells. In terms of oxygen enhancement ratio (OER), the experimental data behaviour can be reproduced, including dependence on particle type at the same linear energy transfer (LET). Errors on the cell survival prediction are of the same order of magnitude than for the original MK model. Our adaptation makes it possible to account for hypoxia without modelling the OER as a function of the LET of the particles, but directly accounting for hypoxic cell survival data.